Proyectos de la fundación para la promoción científica Edbertho Leal Quirós en Macaravita-Santander, Edificio de apoyo del observatorio astrofísico Stellarium. - Lineros Orejarena, Claudia Patricia; Daza Pérez, Ivonnette Veruzka (Universidad Antonio Nariño, 2024)
The present work focuses on the design of the Support Building of the Stellarium Astrophysical Observatory in Macaravita, Santander, promoted by the Foundation Edbertho Leal Quirós and the municipal mayor's office. The project aims to promote astronomy and science, taking advantage of theideal conditions of Macaravita for stargazing. It will be a center for scientific dissemination and education that seeks to bring science closer to the community and contribute to the cultural development of the region.